Distance Learning in the Theme Nanoscience and Nanotechnology applied to Health Area: Perspectives and Interprofessionalism - Bellucci, Jackeline Neres; Silva Bellucci, Felipe; Lacerda Santos, Gilberto (EDU REVIEW. International Education and Learning Review / Revista Internacional de Educación y Aprendizaje, 2020)
Teaching by means of distance learning has grown rapidly in the last few years, allowing Brazilians access to improved higher education in their own country. However, certain challenges exist when it comes to teaching complex, contemporary issues such as Nanoscience and Nanotechnology (N&N). A certain amount of reflection is still required. The objective of this paper is to analyse teaching methods used in distance learning in the fields of N&N which are applied in the areas of health science, with special emphasis on potential, strengths and peculiarities. Issues such as: (i) collaborative learning and (ii) difficulties and opportunities of using distance learning in N&N, among other topics, are presented and discussed. The results indicate the potential use of distance learning in this field of study. Special attention is devoted to the multidisciplinarity and interprofessionalism of the subject as well as to the heterogeneous background of the students and the high level of abstraction.